Evaluation of Road Traffic Energy Harvesting Using Piezoelectricity - Priestner, G. S; Nouri, H (Review of Energy Technologies and Policy Research, 2017)
In modern day society, cleaner, more sustainable forms of electrical power are needed to keep costs lower and to ensure a healthier environment for future generations. The use of piezoelectric devices installed within a road would enable the capturing of kinetic energy from automobile traffic. This energy can then be converted into electrical energy and can be used to offset some of the power coming from the main grid. Such a source of power can also be used to operate road lighting and signage systems, or it could be injected to the grid at an appropriate Point of Common Coupling (PCC). This paper discusses investigation of energy harvesting from piezoelectric materials when installed in a road. The work includes conversion of kinetic energy to electrical using piezoelectric materials, the energy harvesting method, and experimental research on piezoelectric materials.